Determination of selected acute phase proteins during the treatment of limb diseases in dairy cows - P. Jawor; S. Steiner; T. Stefaniak; W. Baumgartner; A. Rzasa (Veterinární Medicína, 2008)
The purpose of this study was to assess the diagnostic value of fibrinogen, haptoglobin, and serum amyloid A determination in the monitoring of the treatment of limb diseases in dairy cows. Fourteen lame cows were examined, while 10 clinically healthy cows constituted the control group. Blood samples from the ill animals were collected on three occasions: (1) upon arrival at the clinic, (2) between the third and sixth day after arriving, and (3) upon return to the owner. Blood samples from the control cows were collected once. Plasma levels of fibrinogen, haptoglobin, serum amyloid A, and total serum protein and its fractions (albumin, α-, β-, γ-globulins) were measured. Significantly higher fibrinogen, haptoglobin, and serum amyloid A levels were observed in the affected cows upon arrival at the clinic than in the control cows. Based on the changes in fibrinogen, haptoglobin, and serum amyloid A concentrations, the cows were divided into those with a systematic decrease in acute-phase protein levels during treatment (Group I, n = 6) and those which showed an increase in one or more acute-phase proteins despite treatment (Group II, n = 8). A stepwise decrease in the examined acute-phase proteins was observed in the first group and indicated an uncomplicated course of treatment; however, treatment of the second group did not appear to be wholly successful. A majority of the cows under treatment (n = 13) exhibited abnormal levels of the examined acute-phase proteins upon return to the owner. This indicates that these patients did not recover completely. The monitoring of plasma acute-phase protein concentrations can be a valuable complement to the clinical assessment of the treatment course and in the early detection of disease complications.